ANALISIS EFISIENSI PASAR MODAL SYARI’AH DAN KONVENSIONAL BENTUK LEMAH BURSA EFEK INDONESIA - Aprinta Trisna Mujisukamto; Aftoni Sutanto (Jurnal Fokus Manajemen Bisnis, 2014)
The analysis in this study was to test the efficiency of the Indonesian capital market in the form of weak. this research has two objeactives, the first objectives is analyze whether Indonesia capital market (convensional and syari’ah) has been efficient (weak-form). The second one is to analyze differentiation efficient market between convensional and syari’ah capital market. This study uses monthly stock price data, from 23 conventional stocks included in the index LQ45 and 2 Islamic stocks included in the index during the observation period 2012-2013 JII. To test the hypothesis efficiency of capital markets weak form using the Run Test, this test is used to test randomness stock price changes. Results from this study are in the period 2012-2013 of conventional and islamic capital market is efficient in the weak form and analyze by looking for a random number of shares on the capital market conventional and islamic capital market, the results showed that there were 22 (95.7%) share price conventional random and 2 (100%) the share price of sharia are random. Based on the analysis of Islamic capital markets more efficient than the conventional capital market.